Examination of Tensile Test Specimens Produced in Three-Dimensional Printer - Kartal, Fuat (Crimson Publishers, 2018)
Buçalışmada, PLA tipi filament kullanılan açık kaynak kod ve ekipmanlardan oluşaneklemeli imalat ile üretilmiş çekme testi numuneleri üzerinde değişikparametrelerin farklı seviyelerdeki etkisi deneysel olarak incelenmiştir. Çekmenumuneleri, ASTM IV tipi çekme testi standartlarına göre tasarlanmış veüretilmiştir. Deney planı, Taguchi yönteminin L9 orthogonal dizisi esasalınarak oluşturulmuş ve deneyler bu plana göre tasarlanmıştır. Elde edilensonuçlar, katman kalınlığı ve dolum tarama aralığı parametrelerinin çekmemukavemetinin artışında önemli oranda iyileştirme sağlayan parametrelerolduğunu göstermektedir.

In this study,the effect of different parameters on tensile test specimens produced by jointmanufacturing with open source code and equipment using PLA type filament wasinvestigated experimentally. Tensile specimens was designed and manufacturedaccording to ASTM IV type tensile test standards. The test design was based onthe L9 orthogonal array of the Taguchi Method and experiments was designedaccording to this plan. According to the results, Parameters of layer thicknessand filling scan range parameters were found to provide significant improvementin the tensile strength increase.
Keywords: Engineering; Fused Depozisyon Modelleme; Deneysel Tasarım; Eklemeli Üretim; Katmanlı İmalat; Parametrik Optimizasyon; Mühendislik; Fused Deposition Modeling; Experimental Design; Additive Manufacturing; Layered Manufacturing; Parametric Optimization